Produtividade e qualidade dos frutos de cultivares de melão submetidos a diferentes doses de bioestimulantes - Gois, Clara Alana Rocha Santos (Universidade Federal Rural do Semi-Árido, 2016)
The melon crop stands out as one of the main fruits exported by agribusiness and an important aspect to highlight is the post-harvest fruit quality. For good production and quality required, producers are increasingly using new technologies. Among these technologies, there have been several theories advocating the use of biostimulants. In this sense, the present study aims to evaluate the influence of biostimulants on productivity and postharvest quality of different varieties of melon in response to different doses and products. Three experiments were developed (one for each cultivar) under field conditions at Dina Dinamarca Industrial Agrícola LTDA., in the municipality Mossoró/RN. The cultivars were ‘Goldex Yellow’, Orange County and sapo skin 15/00. The experimental design was DBC, and the treatments for each cultivar were made up of two biostimulants (Isabion and Quantis) and two witnesses, one without biostimulant (control treatment) and another with application of Crop-SET® (standard producer) with 4 repetitions each. For Isabion how many products and repeated dosages were 250 mL/ha, 500mL/ha, 1000mL/ha and 2000mL/ha for Crop-set the recommended dosages that was used is 1000ml /ha. In each treatment the following characteristics were evaluated: yield, fruit weight, fruit shape, internal cavity, pulp thickness, firmness, soluble solids (SS), titratable acidity (TA), pH, total sugars and SS/TA ratio. The yield was not influenced by the use of biostimulants; the treatment without biostimulant obtained greater firmness and soluble solids content for cultivar Goldex; The Isabion obtained higher soluble solids to the County and 15/00 cultivars, and most SS/AT for all cultivars. The Treatment with Quantis generated more firmness in fruits of cultivars County and 15/00, and lower internal cavity to cultivate County. The recommended dose for the cultivar Goldex was 250mL/ha for Isabion and Quantis products; for cultivar County, doses of 500 mL/ha of Isbaion and 2000ml/ha Quantis; and for cultivar 15/00, 250 mL/ha for Isabion and Quantis
Productivity and fruit quality of melon cultivars submitted to different doses of biostimulants
Keywords: Cucumis melo L; Bioestimulantes; Produtividade; Qualidade de frutos; Cucumis melo L; Biostimulant; Productivity; Fruit Quality; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA